Managing the Unexpected in Otologic Surgery. (2nd September 2014) - Monfared, Ashkan; Blevins, Nikolas H.; Lalwani, Anil K.; Lustig, Lawrence R.; Tucci, Debara L.
Abstract : Program Description: Sponsored by the American Neurotology Society, this interactive presentation aims to provide general practitioners tips and techniques employed by experts in management of intraoperative complications encountered during common otology cases such as tympanoplasty, tympanomastoidectomy, and stapedotomy. The panelists will present illustrative cases and discuss best practice approaches to intraoperative cerebrospinal fluid (CSF) leak and encephaloceles, facial nerve injury, vascular complications, stapedotomy challenges, ossicular chain and external auditory canal damage, and inner ear violation. Educational Objectives: (1) Recognize unexpected circumstances and anatomic variations that could lead to complications in otologic surgery. (2) Manage intraoperative complications such as facial nerve palsy, vascular injury, encephaloceles, CSF leaks, postoperative sensorineural hearing loss, and vertigo.